2012
DOI: 10.1371/journal.pone.0044299
|View full text |Cite|
|
Sign up to set email alerts
|

Reciprocal Regulation of Annexin A2 and EGFR with Her-2 in Her-2 Negative and Herceptin-Resistant Breast Cancer

Abstract: Alternative survival pathways are commonly seen to be upregulated upon inhibition of receptor tyrosine kinases (RTK), including Her-2. It is established that treatment with Herceptin leads to selective overexpression and activation of epidermal growth factor receptor (EGFR) and Src which further contributes to oncogenesis in Herceptin resistant and triple negative breast cancer (TNBC) patients. Here, we show a co-regulated upregulation in the expression of Annexin A2 (AnxA2), a known substrate of Src and one o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
86
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(96 citation statements)
references
References 57 publications
8
86
2
Order By: Relevance
“…EGFR plays a role in regulating ANXA2 phosphorylation and localization (30,31). By coimmunoprecipitation assay, we found that p37 interacted with both ANXA2 and EGFR (Fig.…”
Section: Egfr Facilitates M Hyorhinis Infectionmentioning
confidence: 76%
“…EGFR plays a role in regulating ANXA2 phosphorylation and localization (30,31). By coimmunoprecipitation assay, we found that p37 interacted with both ANXA2 and EGFR (Fig.…”
Section: Egfr Facilitates M Hyorhinis Infectionmentioning
confidence: 76%
“…We found that M. hyorhinis upregulated Tyr23 phosphorylation of ANXA2 and its membrane recruitment. It was reported that EGFR plays a role in regulating ANXA2 phosphorylation and localization [16] . Moreover, our previous work reported that both M. hyorhinis infection and recombinant p37 treatment could activate EGFR [5,12] , but the role of EGFR in M. hyorhinis infection and M. hyorhinis-induced metastasis are not fully elucidated.…”
Section: Identification Of the Microbial And Host Factors Mediating Mmentioning
confidence: 99%
“…There are presently documented eight cofactors for HPV 16 entry into epithelial cells that contribute to selective mucotropism. These include: (1) clathrin coated vesicles, (2) endocytosis, (3) transport protein particle subunit 8, (4) a negative charge molecular display on entry membrane, (5) annexin A2 expression, (6) integrinsα 6 ÎČ 14 expression, (7) cyclophillin B activity and (8) growth factor receptors activation, such as EGFR, and tetraspanins [18][19][20][43][44][45]. In addition entry event studies for HPV 16 in HOK are sadly lacking.…”
Section: Experimental Design To Evaluate Oral Commensal Streptococcusmentioning
confidence: 99%
“…proliferation following low level (e.g., 5%,v/v, 50 mg/mL.) ETOH treatment will increase expression of Annexin A2, and EGFR to also enhance HPV 16 entry [13,14,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32].…”
Section: Set Of Comparative Assays To Examine Associations Of S Salimentioning
confidence: 99%
See 1 more Smart Citation